New combinations in Balkans Clinopodium (Lamiaceae) - Iamonico, Duilio; Bogdanović, Sandro (Phytotaxa, 2014)
To accommodate the morphological diversity of Satureja s.l. (Lamiaceae, Nepetoideae, Menthae, Menthinae), many taxonomists (Bentham 1848, Boissier 1879, Ball & Getliffe 1972, Davis 1982) assign the species of this genus to different genera, mainly Satureja Linnaeus (1753: 587), Clinopodium Linnaeus (1753: 587), Acinos Miller (1754: without pagination), Calamintha Miller (1754: without pagination), and Micromeria Bentham (1829: ad tab 1282, no. 17), while others recognize only Satureja (e.g., Greuter et al. 1984) or Clinopodium (e.g., Kuntze 1891). Recent molecular studies (Wagstaff & al. 1995, Prether & al. 2002, Harley & al. 2004, Trusty & al. 2004, Bräuchler & al. 2005) have contributed to a better understanding of the group and they favoured abandonment of the concept of Satureja sensu lato. As consequence, the genera Acinos, Calamintha and Micromeria p.p. were transferred to the genus Clinopodium and several new combinations were validated both for the Americas (Cantino & Wagstaff 1998, Govaerts 1999, Harley & Paucar 2000, Pool 2008) and for Europe (Rosselló 2006, Bräuchler & al. 2008a, 2008b, Peruzzi & Conti 2008, Brullo & Brullo 2009, Bartolucci & Conti, 2011, 2012).